Switching to different generic medicines: a checklist for safety issues. Issue 2 (4th October 2012) - Becker, Matthijs L; Al Hadithy, Asmar F Y; van den Bemt, Patricia M L A; Hunfeld, Nicole G M
Abstract : Competition between commercially available generics results in lower prices and reduction of healthcare costs. However, the introduction of a new generic product may result in problems with the application in clinical practice. We composed a checklist to survey the differences between products. With this checklist we aim to detect properties of the alternative generic drug that might be problematic in clinical use. Timely prediction of the potential problems supports careful selection and introduction of the appropriate generic drug in the clinic. In this article, we discuss the different items in our checklist and mention some of the problems we have encountered in the last few years. We believe that by using this checklist, hospital pharmacists are better able to make the most appropriate choice of a generic drug for the local requirements of a hospital.